HUBUNGAN PELAKSANAAN JENJANG KARIR PERAWAT PELAKSANA DENGAN KEPUASAN KERJA DI RUMAH SAKIT UMUM DAERAH CIMAHI - Haryanto, Mokhamad Sandi; Nurhidayah, Siti (JURNAL KEPERAWATAN, 2023)
Background: The development of a nurse’s career path is the planning and implementation of a career plan that can be used for Nurses’ placement based on their expertise based and career level with reference to regulations made by the Minister of Health of the Republic of Indonesia to prevent job dissatisfaction or workforce resignation. Objective: The purpose of this study was to determine the relationship between the implementation of the career path of nurses and job satisfaction in the inpatient room of the Cibabat Cimahi Regional General Hospital. Methods: The method used a descriptive correlation method with a cross-sectional approach. This study included 113 Nurses. The Minnesota Satisfaction Questionnaire for job satisfaction and the applicable SPO (Standard Operating Procedure) format were used to collect the data. Data analysis used Chi-Square test to measure the significance of the study. Results: The results showed that there is a relationship between the implementation of the career path of implementing nurses and job satisfaction (<0.000) in the inpatient room of the Cibabat Cimahi Regional General Hospital in 2022. Conclusion: Career path implementation related to Job satisfaction. Further research about other factors that contributed to job satisfaction needs to be done. Keywords: Diabetes Mellitus; Dietary Compliance; Quality of Life.